LABOR AND BANKING SECTOR REFORMS IN NIGERIA - Idowu Oluwatoyin Frederick (European Scientific Journal, ESJ, 2012)
The regime of banking sector reforms leading to recapitalization and consolidation in Nigeria and the consequent merger and or acquisition of existing banks into twenty five (25) by 2005, and later eighteen (18) by 2012 brought along their trails attendant labor problems in terms of educational diversity, job security and productivity, decent employment questions. The study review post consolidation performance of the banking sector to assess the extent to which the sector meets consolidation objective using post development approach. It was found that while the alliance and marriage of seemingly compatible partners are settling down, the society is at the receiving end of the severance of labor and the enlargement of the pool of reserved army of the unemployed. The fall-out therefore is double-edge for the economy and the society.